Análise de pictogramas (ícones) em aplicativos de smartphones: o caso do APP Meu Ônibus MOB - São Luís - Soares, Alexsandro Pereira (2016)
This work has as study object the pictograms used in the application "My Bus - MOB". Does the analysis of the recognition of these pictograms by the user, trying to understand how he navigates the graphic interface and how is the process of recognition of graphics. In this study we investigated the pictograms and how they fit into the communication interface issues within the Graphic Design and Human-Computer Interface. As it is graphic interface evaluations were performed through ergonomic usability recommendations for icons, and also two tests involving the user which sought to understand the mental maps that is made from the icons of the labels produced by the application "My Bus - MOB" Production using the method presented by Krampen and ISO comprehension test 9186: 2001. So with the research done by the research can demonstrate the need for icons projetacão with user input in the design process in order to design icons with simple features, with a small number of elements in its visual construction to minimize noise in communication.